2020
DOI: 10.1016/j.hrthm.2020.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility for subcutaneous implantable cardioverter-defibrillator in congenital heart disease

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…
We thank Wang et al for their interest in our article on S-ICD eligibility in adults with congenital heart disease (ACHD). 1 Wang et al emphasize that our results are in contrast to several previous ACHD studies, [2][3][4][5] including one recent study from their group. 2 Carefully reviewing the references, our results regarding S-ICD eligibility in ACHD patients (83%) are obviously in line with previous published data.
…”
contrasting
confidence: 96%
See 1 more Smart Citation
“…
We thank Wang et al for their interest in our article on S-ICD eligibility in adults with congenital heart disease (ACHD). 1 Wang et al emphasize that our results are in contrast to several previous ACHD studies, [2][3][4][5] including one recent study from their group. 2 Carefully reviewing the references, our results regarding S-ICD eligibility in ACHD patients (83%) are obviously in line with previous published data.
…”
contrasting
confidence: 96%
“…8,9 The ECG-based screening test was performed as standard of care, but was not the main focus of our study, since this has already been largely examined in ACHD patients in previous studies. 2,3,5,7,10 Furthermore, Wang et al propose a comparison of S-ICD eligibility in different positions (standing and supine) on the left and right parasternal position using McNemar's chi-square test. Clinicians performing S-ICD screening will agree, that the proposed analysis comparing S-ICD eligibility in different positions is irrelevant in clinical practice, since S-ICD eligibility is only met if at least one vector is eligible in both, supine and standing position.…”
mentioning
confidence: 99%
“…Alonso et al conducted a study to test S-ICD eligibility specifically in congenital heart disease patients at high risk of sudden cardiac death and only 44% of the significant risk subgroup were eligible for an S-ICD [19]. In another study by Wang et al, 101 mostly complex congenital heart disease patients were screened for eligibility for S-ICD and only 61 patients (60%) were deemed eligible for S-ICD screening [20]. In another study by Garside et al, 102 complex ACHD patients were recruited and 75.4% of ACHD patients met the screening criteria for an S-ICD [21].…”
Section: S-icd Screening Eligibility and Inappropriate Shocks Ratesmentioning
confidence: 99%
“…The limitations in the study design and conduct could at least partially explain the difference in the reported results with other studies. [2][3][4] Also, the study 1 raised questions about the appropriateness of utilized statistical analyses. For appropriate paired comparison of S-ICD ineligibility in different positions (standing and supine) on the left and right sides, McNemar's χ 2 statistic has to be used.…”
mentioning
confidence: 99%
“…Similar to the discussed study, previous studies of S-ICD eligibility in ACHD are relatively small. [2][3][4][5] To summarize research evidence, future systematic reviews and meta-analyses will likely be needed. An accurate, detailed, and reproducible methods and results have the greatest impact on what new studies can expand on in the ACHD population.…”
mentioning
confidence: 99%